Persepsi Metode Pembelajaran Daring Dengan Motivasi Mahasiswa Sekolah Tinggi Ilmu Kesehatan Majapahit - Dwiharini Puspitaningsih; Siti Rachma (MEDICA MAJAPAHIT, 2020)
The COVID-19 pandemic has an impact on several policies including on learning patterns. E-Learning can be an alternative solution to learning problems. Motivation is considered an important factor for learning success, including in the online learning environment, so it is necessary to reconsider the motivation to learn in learning environments that use technology. However, the academic community is not yet accustomed to using a blended and fully online learning system. The research objective was to determine the relationship between perceptions of online learning methods and motivation of students at the Majapahit College of Health Sciences. This research was a quantitative study, using a correlation analytic design, with a sample size of 153 respondents. The bivariate analytical test in this study used the technical rank correlation or often called the Spearman rank correlation test. The results showed a positive perception of the respondents, namely the aspects of teaching and learning in online learning, 68.6% positive, 74.6% of students' perceptions of aspects of positive lecturers' abilities, and 72.7% of students' perceptions of the aspects of facilities and infrastructure in online learning is positive. Based on the results of the study showed that most of the respondents had strong motivation (35.7%). With the statistical test of the Spearman Rank Test, the results obtained p value 0.00002 <α 0.05 with Correlation Coeffient (correlation coefficient) of 0.639, it was found that there was a strong relationship between perceptions of online learning methods and the motivation of STIKes Majapahit students. The teaching and learning process will run effectively and efficiently if it is supported by the availability of supporting media. Provision of media and educational methodologies that are dynamic, conducive and dialogic are needed for the optimal development of the potential of students